REMEDIASI MISKONSEPSI SISWA PADA MATERI TEKANAN MENGGUNAKAN MODEL PEMBELAJARAN LEARNING CYCLE 7E BERBANTUAN ALAT PERAGA - Arjuna, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrakThis research was aimed to know the effectiveness of learning cycle 7E assisted props in reproducing students? misconceptions of pressure in SMP Negeri 13 Pontianak. The method of this research was quasi experimental design with nonequivalent control group design. The sample consisted of class VIII H students as experiment group I and class VIII D as experiment group II. The instrument of data collection was using diagnostic like multiple choices without reasons. There were lowering students? misconceptions on experiment group I from 61.90% to 6.67% and on experiment group II from 74.51% to 29.41%. There were significant alteration based on McNemar test on experiment group I (?2score= 46.08 > ?2table= 3.84) and experiment group II (?2score= 41.89 > ?2table= 3.84). The test result showed that (Zscore= 0.26 < Ztable= 1.69) mean remediation using learning cycle 7E assisted props as effective as without assisted props. This research was hoped can be a reference and information in doing remediation to improve students? misconceptions.Keywords: Remediation, misconception, learning cycle 7E, props, pressure